Pencegahan Bullying Melalui Layanan Informasi di Yayasan Darul Hikmah Kabupaten Pandeglang Banten - Khairat, Imalatul; Lailatul Ula, Ratu Sita; Fizrianti, Dila; Nurdiana, Ina; Subhan, Ahmad (Indonesian Journal of Educational Counseling, 2025)
This study aims to increase students' understanding of information services in addressing Bullying at the Darul Hikmah Foundation, in Pandeglang Regency. The subjects in this research involved 30 students from the foundation as participantsUtilizing the Participatory Action Research (PAR) method, this study integrates the research process with social change efforts. PAR involves identifying a problem, conducting research to address it, and implementing solutions through action. Data collection inclued interviews and direct observation involving students, leaders, and Foundation administrators. The findings reveal that students at the Darul Hikmah Foundation have developed on understabdibf of Bullying is effects and strategies for prevention. Information service activities provided valueable learning opportunities, equipping oarticipants tith knowledge about Bullying prevention and empowering them to resist and prevents such behaviour in their environment.